Natural product nanozymes of herbal extract galangin in managing hepatocellular carcinoma - Wang, Erhao; Wu, Yuxia; Wang, Yan; Li, Jiao; Liang, Xiuzhen; Wang, Zhongtao; Liu, Xiaofei; Feng, Faming; Mao, JianCang; Zhu, Yingqi; Li, Le (Frontiers in Chemistry, 2024)
Numerous local herbal extract species have been investigated as potential medicinal ingredients due to their promising anti-cancer properties. However, the primary constraint of the class of plant flavonoids lies in their low solubility and limited membrane permeability, leading to chemical instability and restricted bioavailability that impede biomedical applications. In this study, we have developed an ideal nanozyme-Galazyme, comprising galangin-loaded copper Nanozyme coated by DSPE-PEG, which amplifies oxidative stress to induce apoptosis via the regulation of reactive oxygen species (ROS) generation and mitogen-activated protein kinase (MAPK) activation. Galazyme exhibited significant peroxidase mimetic activity, demonstrating its potential to generate ROS and elevate oxidative stress. Upon uptake by HepG-2 cells, Galazyme efficiently converts excess hydrogen peroxide (H2O2) into highly reactive •OH radicals and upregulates MAPK expression, leading to the activation of Bax and Caspase 3, thereby promoting irreversible tumor cell apoptosis. Both in vitro and in vivo results demonstrate that Galazyme inhibits tumor cell growth and induces apoptosis by generating ample ROS and activating the MAPK pathway. Our study offers novel evidence supporting the enhancement of Galazyme-induced apoptosis through the upregulation of Bax and Caspase 3, along with the elucidation of the interaction between MAPK and apoptosis.